Intracranial Meningioma Diagnosed during Pregnancy Caused Maternal Death - Zehra Kurdoglu; Orkun Cetin; Ismail Gulsen; Deniz Dirik; M. Deniz Bulut (Case Reports in Medicine)
Brain tumors are rarely diagnosed during pregnancy. Accelerated growth of intracranial meningiomas during pregnancy sometimes requires urgent surgical intervention. We describe a 41-year-old pregnant woman with severe neurological decompensation requiring immediate neurosurgery. Cesarean section resulted in maternal death. Meningioma diagnosed during a viable pregnancy should be managed according to the severity of maternal neurological symptoms and gestational age of pregnancy. Early intervention for intracranial tumors during pregnancy may save maternal and fetal lives.